Quantifying bacterial adhesion on antifouling polymer brushes via single-cell force spectroscopy1. Issue 31 (21st August 2015) - Rodriguez-Emmenegger, Cesar; Janel, Sébastien; de los Santos Pereira, Andres; Bruns, Michael; Lafont, Frank
<x xml:space="preserve">Abstract</x> The adhesion forces between a single bacterial cell and different polymer brushes were measured directly with an atomic force microscope and correlated with their resistance to fouling.